Honduras : Request for Stand-By Arrangement-Staff Report; Staff Statement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Honduras. (IMF Staff Country Reports; Country Report, 2008)
This paper discusses request from Honduras' authorities for a Stand-By Arrangement (SBA). Honduras has had three previous Poverty Reduction and Growth Facility (PRGF) arrangements, the last of which ended in February 2007. The most recent PRGF program focused on fiscal consolidation and structural reforms. However, the program went off track owing to large wage increases granted in 2006, including a four-year agreement with teachers. The authorities are now requesting a 12-month SBA covering economic policies through December 2008. In IMF staff's view, the authorities' program appropriately addresses emerging imbalances.